2007
DOI: 10.17221/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of limestone soil-forming substrate in the forest ecosystem classification

Abstract: AbstrAct:The uniqueness of limestone soil-forming substrate was assessed with respect to the classification of forest ecosystems. 50 soil profiles from the Bohemian Karst were studied and the results were confronted with previously published works from other karst areas. The evaluation of soil profiles was based on a macroscopic description, on the results of chemical and physicochemical analyses, and on a micromorphological study. The carbonate bedrock was a cause of specific genesis of soils in these sites -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Site types were usually identical with individual edaphic categories of the PNV system, but we made exceptions in well-founded cases (e.g. it is difficult to separate FTs 2B9, 2W1, 2W3 in karst regions -Šamonil 2005, 2007aŠamonil, Viewegh 2005). These ST types were established specifically for this study and are not a part of the PNV system.…”
Section: Field Samplingmentioning
confidence: 99%
“…Site types were usually identical with individual edaphic categories of the PNV system, but we made exceptions in well-founded cases (e.g. it is difficult to separate FTs 2B9, 2W1, 2W3 in karst regions -Šamonil 2005, 2007aŠamonil, Viewegh 2005). These ST types were established specifically for this study and are not a part of the PNV system.…”
Section: Field Samplingmentioning
confidence: 99%
“…In research covering more than 1800 soil profiles from the entire territory of Germany, Grüneberg et al (2014) confirmed the higher content of organic matter in soil rich in carbonates both for plains and uplands, and for mountainous areas (Table 1). Even if higher concentration of organic carbon (OC) was recorded in soils neighbouring the rendzinas, the stock of OC in rendzinas was higher due to thicker humus horizons (Drewnik 1998, Šamonil 2007, Wasak 2017. Also the analysis of the morphology of organic and humus horizons and their classification showed that rendzinas contain specific humus forms absent in other soils (Kubiena 1953, Miechówka 2002, Ponge et al 2011, Jabiol et al 2013, Zanella et al 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%